PENGARUH MODEL PEMBELAJARAN INKUIRI DAN MOTIVASI TERHADAP HASIL BELAJAR PKn SISWA KELAS VII SMP NEGERI 3 BALIGE KABUPATEN TOBA - Sidabutar, Reventan Ricardo; Napitupulu, Efendi; Sudrajat, Ajat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: 1) determine the effect of the inquiry learning model on students' civics learning outcomes; 2) determine the effect of motivation on students' civics learning outcomes; and 3) determine the interaction of the inquiry learning model and motivation on students' civics learning outcomes of class VII SMP Negeri 3 Balige, Toba Regency. The study was conducted at SMP Negeri 3 Balige, Toba Regency. The study population consisted of 125 students from class VII (A, B, C, D). The sampling technique used was cluster random sampling. The total sample was 64 students. The experimental sample of class VII A consisted of 32 students, and the control class consisted of 32 students. The research instruments used to assess students' civics learning outcomes included a multiple-choice test and a questionnaire evaluating student motivation. The trial of the learning outcome test was conducted on 28 students of class VIII A, and 20 valid and reliable test questions were obtained. The student motivation questionnaire was administered to 31 students of Class VII C. The results of the trial of the motivation questionnaire obtained 26 valid and reliable statements. This study employs a quantitative approach, utilizing an experimental method (two-group pretest-posttest control group design) and a two-way analysis of variance (2x2 ANOVA). The prerequisite analysis tests are met, namely the normality test and the homogeneity test. Hypothesis testing uses 2x2 ANOVA. The results of the study are 1) the effect of the inquiry learning model on students' Civics learning outcomes, the F count>F table is 95.863>2.76 (sig.000 <0.05); 2) the effect of motivation on students' Civics learning outcomes, F count>F table is 242.922>2.76 (sig.000<0.05); and 3) the interaction between the learning model and students' motivation on students' Civics learning outcomes, F count>F table is 21.716>2.76 (sig.000<0.05). The conclusions of the study are 1) There is an effect of the inquiry learning model on students' Civics learning outcomes; 2) There is an influence of motivation on students' civics learning outcomes. 3) There is an interaction between the learning model and student motivation on the civics learning outcomes of grade VII students at SMP Negeri 3 Balige, Toba Regency.